Association of Anxiety/Depressive Symptoms with Psychotic-like Experiences: The Moderation Effect of Sex and Resilience - Manling Long; Peiyu Zhang; Jingyu Shi (MDPI AG, 2024)
Background: Psychotic-like experiences (PLEs) are a part of the continuum of psychosis and are common in the general population. While most of these experiences are transient, they are strongly correlated with an increased risk of various adverse psychological outcomes. Anxiety and depressive symptoms also occur frequently in the adolescent population. Much research has previously demonstrated a correlation between these two symptoms and PLEs. However, few investigations have examined what influences this association, and sex and resilience may be important moderators. Methods: This study selected a sample of first-year students from a university in Shanghai. A total of 2970 adolescents completed questionnaires measuring sociodemographic characteristics, anxiety/depressive symptoms by SCL-90, resilience by CD-RISC, and self-reported PLEs by PQ-16. Results: The findings indicated that PLEs were prevalent in the sample, with at least one PQ-16 item present in 42.5% of individuals. Anxiety/depressive symptoms were significantly associated with PLEs, and there was a sex difference in this association (p < 0.001). What is more, this relationship was stronger in males than in females. Additionally, we found a significant interaction (p < 0.001) between resilience and anxiety/depressive symptoms when looking at the correlates of PLEs. Those with stronger resilience showed a considerably weaker connection between PLEs and symptoms of anxiety and depression. Conclusions: These findings can potentially inform the development of targeted new clinical interventions.